Increasing the Formation of Active Sites on Highly Crystalline Co Branched Nanoparticles for Improved Oxygen Evolution Reaction Electrocatalysis. Issue 11 (29th April 2020) - Myekhlai, Munkhshur; Benedetti, Tania M.; Gloag, Lucy; Gonçales, Vinicius R.; Cheong, Soshan; Chen, Hsiang‐Sheng; Gooding, J. Justin; Tilley, Richard D.
Abstract: The electrocatalysis of the oxygen evolution reaction (OER) at the surface of oxidized metal electrocatalysts is highly dependent on the structure and composition of the surface oxide. Here, Au core‐ Co branched nanoparticles were synthesized using a cubic‐core hexagonal‐branch growth approach in a slow reductive solution synthesis, resulting in highly crystalline metallic hcp Co branches. Electrochemical surface oxidation of the Co branched nanoparticles resulted in formation of Co(OH)2 that enable the formation of a higher number of active sites under OER conditions compared to Co3 O4 . Differently from polycrystalline spherical Au−Co core‐shell nanoparticles, the oxidized structure on the Co branched nanoparticle surface is retained with electrochemical cycling, resulting in improved OER activity and stability. Abstract : Making room for more active sites : Au core‐ Co branched nanoparticles were synthesized using a cubic‐core hexagonal‐branch growth approach in a slow reductive solution synthesis, resulting in highly crystalline metallic hcp Co branches. Single crystalline Co nanoparticles retain a surface oxide composition during electrochemical cycling that enable the formation of more active sites for OER, resulting in improved activity and stability.